Understanding the Role of Commercial Separators and Their Reactivity toward LiPF6 on the Failure Mechanism of High‐Voltage NCM523 || Graphite Lithium Ion Cells. Issue 2 (2nd December 2021) - Klein, Sven; Wrogemann, Jens Matthies; van Wickeren, Stefan; Harte, Patrick; Bärmann, Peer; Heidrich, Bastian; Hesper, Jakob; Borzutzki, Kristina; Nowak, Sascha; Börner, Markus; Winter, Martin; Kasnatscheew, Johannes; et al.
Abstract: NCM523 || graphite lithium ion cells operated at 4.5 V are prone to an early "rollover" failure, due to electrode cross‐talk, that is, transition metal (TM = Mn, Ni, and Co) dissolution from NCM523 and deposition at graphite, subsequent formation of Li metal dendrites, and, in the worst case, generation of (micro‐)short‐circuits by dendrites growing to the cathode. Here, the impact of different separators on the high‐voltage performance of NCM523 || graphite cells is elucidated focusing on the separators' structural properties (e.g., membrane vs fiber) and their reactivity toward LiPF6 (e.g., ceramic‐coated separators). First, the separator architecture has a major impact on cycle life. Fiber‐structured separators can prevent the "rollover" failure by a more homogeneous deposition of TMs and formation of Li metal dendrites, thus, hindering penetration of dendrites to the cathode. In contrast, porous membrane‐structured separators cannot prevent the cell failure due to inhomogeneous TM deposits/Li metal dendrites. Second, it is demonstrated that different types of ceramic‐coated separators (Boehmite (γ‐AlO(OH)) vs α‐Al2 O3 ) exhibit different reactivities toward LiPF6 . While α‐Al2 O3 shows a minor reactivity toward LiPF6, the γ‐AlO(OH) coating leads to in situ formation of the beneficial difluorophosphate anion in high amounts due the high reactivity toward LiPF6 decomposition, which significantly improves cycle life. Abstract : High‐voltage operated NCM523 || graphite lithium ion battery cells suffer from severe capacity fading, as a result of transition metal (Ni, Co, and Mn) dissolution from NCM523 and deposition at graphite, subsequently inducing Li metal formation. The impact of the separator architecture and the separators' reactivity toward LiPF6 decomposition, which can result in in situ formation of the additive difluorophosphate are demonstrated.